Women's perspectives on relationship dynamics with their partners and their role in HIV acquisition, HIV disclosure, hormonal contraceptive uptake, and condom use. Issue 1 (2nd January 2021) - Chapola, John C; Hatfield-Timajchy, Kendra; Bula, Agatha K; Hurst, Stacey; Chinula, Lameck; Kourtis, Athena P; Tang, Jennifer H
Abstract : Background : Limited information exists about relationship dynamics and their role in HIV acquisition, HIV disclosure, hormonal contraceptive uptake, and condom use among women in Malawi. Methods : Ninety-seven women aged 18–45 years were randomly assigned to initiate the depot medroxyprogesterone acetate injectable or levonorgestrel implant from May 2014 to April 2015 in Lilongwe, Malawi. Women were recruited after randomisation to participate in semi-structured interviews about HIV and family planning using purposive sampling. Interviews were thematically analysed using within and between group comparisons. Results : We conducted individual interviews and/or focus group discussions with 41 women: 30 (73%) women living with HIV and 11 (27%) women not living with HIV. Most women living with HIV who participated in in-depth interviews disclosed their status to their partners, and most partners agreed to get HIV tested only after disclosure. Nearly all women said their partners agreed to use condoms, but few used them consistently. Nearly all women believed their current and former partners had outside partners. Most women living with HIV who participated in in-depth interviews believed their current or other serious partners were the source of their infection. Some women thought their partner's infidelity was due to their partner's disinterest in sex with them during menstrual/ breakthrough bleeding. Some women included their partners in contraceptive decision-making when the partner was supportive. Discussion : Relationship dynamics affected decision-making for contraceptive and condom use, as well as serodisclosure for the women living with HIV in the study. All women reported challenges with consistent condom use with their male partners, although contraceptive use was generally more acceptable. Women included their partners in their decision-making concerning contraceptive use when they were supportive.